Upaya Pencegahan Penyakit Degeneratif Diabetes Melitus Melalui Pemeriksaan Glukosa Darah Pada Lansia di Posyandu Mawar Merah Kelurahan Labuhbaru Barat Kecamatan Payung Sekaki Pekanbaru - H, Hartini; Yuliandari, Aisyara; Isra’ Huda, Balqies; Triseptian Silalahi, Alfredo (Abdimas Indonesian Journal, 2024)
I The most common degenerative disease in Indonesia is diabetes mellitus (DM). Diabetes Mellitus (DM) is a collection of symptoms characterized by high blood glucose levels (hyperglycemia) caused by a deficiency of the hormone that regulates blood glucose levels (insulin). Elderly people experience natural physiological changes, making them vulnerable to suffering from disease. The prevalence of elderly people with DM in Indonesia increases every year by 6% -6.3%. Efforts that can be made to prevent and control DM include counseling, routine checking of blood glucose levels, eating arrangements, physical activity and pharmacological therapy. One of the efforts made through community service activities by the AKJP II Pekanbaru Service Team is counseling and checking blood glucose levels. This stage of service activities has been carried out in coordination with the Head of the RT and the Mawar Merah Posyandu Team. Counseling is carried out using educational leaflets and discussions. The examination was carried out by collecting data on the identity of the elderly and measuring blood glucose using a POCT tool. Overall, this service activity was successfully carried out referring to the results of the analysis of the service questionnaire with 100% of the elderly participants hoping that the activity could be carried out in a sustainable manner.